Wildfire Risk analysis using Flammap in Semi-Arid Mediterranean Forests - Gheffar Mohammed; Merghraoui Mammar (Ekológia (Bratislava))
This study presents a comprehensive approach to assessing wildfire behavior in a Mediterranean landscape using the FlamMap fire moelling software. We employed geospatial tools to map and categorize land cover types, followed by field visits to validate the remote data and collect detailed vegetation and fuel load information. Key physical parameters, including slope, elevation, and historical weather data, were integrated into the FlamMap model to simulate wildfire behavior under two wind scenarios: one with an average wind speed of 10 km/h and another with a maximum wind speed of 23 km/h. The simulations provided detailed insights into fire behavior parameters such as fireline intensity, flame length, and rate of spread (ROS), emphasizing the critical roles of wind speed, vegetation type, and topography. Results showed significant variations in fire behavior across different vegetation types, with the highest fireline intensities and rates of spread occurring in areas dominated by Aleppo pine and dense shrublands, particularly under high wind conditions. The overlay of historical fire data with simulation results revealed that regions with dense shrub stands and Aleppo pine wooded shrub are most prone to wildfires, underscoring the need for targeted fire management strategies. This study demonstrates the utility of FlamMap in predicting fire behavior and guiding wildfire management efforts in high-risk areas.